2019
DOI: 10.5430/jnep.v9n9p115
|View full text |Cite
|
Sign up to set email alerts
|

Male patients’ gender preferences for hospital nurses

Abstract: There has been limited research exploring the beliefs and attitudes of male patients regarding the gender of their nurses. These attitudes, as well as the factors affecting the gender-preference of male patients, must be explored in a flexible, holistic manner. The objective of our study was to explore key aspects of male patients’ beliefs and attitudes about the gender of their nurses in the hospital setting, as well as the factors that influenced those perceptions. We employed a descriptive, qualitative, cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It is stated that some patient groups have positive opinions about male nurses (Adeyemi-Adelanwa et al, 2015, pp.140-3;Buyuk et al, 2015, pp.729-736). A study conducted on ten male patients by LeBlanc et al (2019) found that participants reported no gender preference for their nurses. And in the same study the majority of patients agreed that the nature of the task did not matter in their preference for a male or female nurse (LeBlanc, Bryanton & Wood, 2019, pp.…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that some patient groups have positive opinions about male nurses (Adeyemi-Adelanwa et al, 2015, pp.140-3;Buyuk et al, 2015, pp.729-736). A study conducted on ten male patients by LeBlanc et al (2019) found that participants reported no gender preference for their nurses. And in the same study the majority of patients agreed that the nature of the task did not matter in their preference for a male or female nurse (LeBlanc, Bryanton & Wood, 2019, pp.…”
Section: Discussionmentioning
confidence: 99%